Distributed approach in fault localisation and service restoration: State-of-the-Art and future direction. Issue 1 (1st January 2019) - Mwifunyi, Rukia J.; Kissaka, Mussa M.; Mvungi, Nerey H.
Abstract: This paper presents a survey of recent development in Fault Localisation and Service Restoration (FLSR) following electrical disturbance in Power Distribution Systems (PDS) based on distributed approaches. Distributed approaches have been found to fit well in the distribution systems as they have more than one decision-making component, and data processing can be done in parallel in individual units that makes it faster and requires less processing capabilities centrally. Recently reported distributed approaches have been studied and analysed. With ever-growing integration of the renewable distributed generation (DG) into the distribution systems, it has been realised that, the uncertainty nature of both load demand and DG need to be considered in the service restoration problems for improved efficiency. Consideration of uncertainty nature of the renewable generation and load demands in the distributed FLSR result into the increased restored customers as well as avoiding overloading and underloading after restoration. The paper starts with a general overview of the Multi Agent Systems (MAS) as the distributed control approach and approaches for forecasting load demand and DG power and then discusses different approaches used for FLSR in PDS by showing their strengths and limitations. The review is concluded by giving future research directions.